Association of Circulating T Follicular Helper Cells With Idiopathic Optic Neuritis and Neuromyelitis Optica Spectrum Disorders - Wu, Qian; Yang, Binbin; Wang, Jiawei (Frontiers in Neurology, 2021)
Background: T follicular helper cells (Tfh cells) play an important role in activating B lymphocytes and may associate with idiopathic Optic Neuritis (ON) and Neuromyelitis Optica Spectrum Disorders (NMOSD). Objective: This study aimed to examine the potential role of Tfh cells in pathogenesis of idiopathic ON and NMOSD. Methods: Circulating CD4+CXCR5+ and CD4+CXCR5+PD-1+ cells in 46 idiopathic ON and 68 NMOSD patients as well as 28 healthy controls were examined by flow cytometry before treatment. Serum AQP4 antibody, Expended Disability Status Scale (EDSS) and Visual Outcome Scale (VOS) were detected before and after treatment. Results: The percentages of circulating CD4+CXCR5+ and CD4+CXCR5+PD-1+Tfh cells in CD4+ cells (%) were significantly increased in idiopathic ON and NMOSD compared with those of healthy controls (p < 0.01). No significant difference of Tfh cells in blood and cerebral spinal fluid (CSF) was found between ON and NMOSD patients. The percentages of CSF, CD4+, CXCR5+, and CD4+CXCR5+PD-1+ cells in CD4+ cells (%) were positively correlated with those of the blood (r = 0.5781, r = 0.6079, p = 0.0076, and p = 0.0045, respectively). EDSS scores of NMOSD group were higher than those of ON group and the time course of NMOSD patients was longer than that of ON patients (p < 0.01). After methylprednisolone treatment, both EDSS and VOS scores were significantly decreased at discharge compared with before treatment (p < 0.01). There was no significant correlation among Tfh cell percentages in CD4+ cells, CSF leukocytes, CSF protein, annual recurrence rate, EDSS and VOS scores between two groups (p > 0.05). Conclusion: The Circulating T follicular helper cells were increased in both idiopathic ON and NMOSD.